PENGARUH PERMAINAN HALANG RINTANG BERBASIS MISI TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK DARUL FALAH PADANG - Rima Fitria; Tisna Syafnita; Rakimahwati; Saridewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of mission-based obstacle course games on the development of gross motor skills in children aged 5–6 years at Darul Falah Kindergarten, Padang. The study was motivated by the finding that children's gross motor skills, particularly jumping, balancing, bending, and eye-hand coordination, had not yet developed optimally. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 38 children from three groups, while the sample comprised 26 children selected through purposive sampling and divided into an experimental group (13 children) and a control group (13 children). Data were collected using a gross motor skills test covering eight indicators and analyzed using Gain Score, the Liliefors normality test, the Levene homogeneity test, the Independent Sample t-test, and Cohen’s d effect size with SPSS 25.0. The results showed a significant difference between the experimental and control groups (p = 0.004), with a large effect size (d = 1.26). Therefore, the MissionBased Obstacle Course Game significantly improved the gross motor development of children aged 5–6 years